2022
DOI: 10.1002/app.52245
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of Cocos nucifera L. peduncle fiber reinforced polymer composites for lightweight sustainable applications

Abstract: The present work aims to investigate the potentiality of reinforcing coconut tree peduncle fiber an agro-waste with unsaturated polyester resin, optimizing its mechanical properties and promote as an alternative reinforcement to harmful synthetic fiber polymer composites. It was found that polymer composites with 40 wt% fiber content exhibited maximum mechanical properties and started to decline on further addition of fibers due to lack of sufficient resin to wet the fibers leading to fiber pull-out and debond… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
20
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

7
2

Authors

Journals

citations
Cited by 34 publications
(21 citation statements)
references
References 45 publications
(63 reference statements)
0
20
1
Order By: Relevance
“…Earlier research outcomes showed that Acacia caesia bark fibers (37 wt%), Cocos nucifera peduncle fiber (50.1 wt%), Cortaderia selloana grass stem fiber (53.7 wt%) and V. maderaspatana fiber (56.12 ± 5.42 wt%) have lower cellulose component than the MAF. [ 39,42 ] Besides this, some of the plant fibers, namely purple bauhinia fiber (60.54 ± 4.31 wt%), E. indica grass fiber (61.3 wt%) and Coccinia grandis L. stem fiber (62.35 wt%) have quite elevated cellulose component than MAF. [ 14,32 ] The existence of a higher quantity of hemicellulose is not an encouraging property as it is an amorphous component.…”
Section: Results and Discussion On Characterization Of Mafmentioning
confidence: 99%
“…Earlier research outcomes showed that Acacia caesia bark fibers (37 wt%), Cocos nucifera peduncle fiber (50.1 wt%), Cortaderia selloana grass stem fiber (53.7 wt%) and V. maderaspatana fiber (56.12 ± 5.42 wt%) have lower cellulose component than the MAF. [ 39,42 ] Besides this, some of the plant fibers, namely purple bauhinia fiber (60.54 ± 4.31 wt%), E. indica grass fiber (61.3 wt%) and Coccinia grandis L. stem fiber (62.35 wt%) have quite elevated cellulose component than MAF. [ 14,32 ] The existence of a higher quantity of hemicellulose is not an encouraging property as it is an amorphous component.…”
Section: Results and Discussion On Characterization Of Mafmentioning
confidence: 99%
“…Scherer's relation was admirable to determine the crystallite size of the optimally surface‐modified fiber, which is given as the Equation (). In this relation, ‘ K ' represents the constant (0.89), ‘ λ ’ indicates the intensity of radiation, ‘ β ’ symbolizes the full‐width at half‐maximum (FWHM) and ‘ θ ’ signifies the Bragg's angle 29 CIgoodbreak=()H200HAMH200, CSgoodbreak=β0.3emcos0.3emθ. …”
Section: Methodsmentioning
confidence: 99%
“…In this relation, 'K' represents the constant (0.89), 'λ' indicates the intensity of radiation, 'β' symbolizes the full-width at half-maximum (FWHM) and 'θ' signifies the Bragg's angle. 29 CI ¼…”
Section: X-ray Diffraction Analysismentioning
confidence: 99%
“…Moisture adsorption on the surface of polymer composites has a substantial impact on their behavior over time. [124][125][126][127][128][129][130] Ogunsona et al [131] investigated nylon/ biocarbon reinforced biocomposites subjected to accelerated aging conditions by immersing the composite in water at 85 C for up to 28 days. The nylon/biocarbon biocomposites absorbed less water than nylon alone implying biocarbon particles operate as a barrier trapping absorbed moisture inside their pores surrounding the nylon interface.…”
Section: Aging Effects On Free Vibration Of Biocomposites In Water Me...mentioning
confidence: 99%